Ab Initio Calculations of the Main Crystal Surfaces of Forsterite (Mg2SiO4): A Preliminary Study to Understand the Nature of Geochemical Processes at the Olivine Interface - Bruno, M.; Massaro, F.; Prencipe, M.; Demichelis, Raffaella; De La Pierre, M.; Nestola, F. (American Chemical Society, 2014)
We present an accurate ab initio study of the structure and surface energy at 0 K of the (010), (101), (111), (001), (110), (120), and (021) faces of forsterite (Mg2SiO4) using the hybrid Hartree–Fock/density functional B3LYP Hamiltonian and a localized all-electron Gaussian-type basis set. According to the surface energy values, the stability order of the forsterite faces was found to be (010) < (120) < (001) < (101) < (111) < (021) < (110). Then, the equilibrium shape of forsterite was drawn and compared with the previous ones obtained at an empirical level. Our results were combined with experimental evidence to develop some considerations about the shape and genesis of olivine included in diamond. They provide crucial information on the diamond formation mechanism with respect to its guest inclusions, a topic that is still under strong debate in the scientific community. In particular, we discuss the peculiar crystal morphology of olivine included in diamond, and we demonstrate that it cannot be considered as evidence of syngenesis (i.e., inclusion and host diamond formed at the same time). Furthermore, if the morphology of olivine is modified during its encapsulation in diamond but it does not show a preferential orientation with respect to diamond, we can state that (i) the bulk of olivine is protogenetic (i.e., a piece of previously formed olivine is encapsulated by the host diamond), whereas (ii) its shape is syngenetic, that is, the morphology is rearranged during the encapsulation.